PENGARUH PEMBERIAN REWARD DAN PUNISHMENT TERHADAP KINERJA PEGAWAI DI PUSKESMAS LAKESSI KOTA PAREPARE - Musfirah, Musfirah (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to examine the effect of reward and punishment on employee performance. The method used is quantitative causal. Data collection carried using a questionnaire instrument was given to the research sample of 80 respondents. The data analysis technique in this study used multiple linear regression analysis. Based on the that has already complete, it shows that: 1) Rewards have a positive and significant effect on employee performance. 2) Punishment does not affect or significantly affect the performance of employees. 3) Reward and Punishment have a positive and significant impact on employee performance.